Prolonged venous transit is associated with worse neurological recovery in successfully reperfused large vessel strokes - Janet Mei; Hamza Adel Salim; Dhairya A. Lakhani; Licia Luna; Aneri Balar; Mona Shahriari; Nathan Z. Hyson; Francis Deng; Adam A. Dmytriw; Adrien Guenego; Vaibhav Vagal; Victor C. Urrutia; et al. (Annals of Clinical and Translational Neurology)
Abstract Objective Venous outflow (VO) impairment predicts unfavorable outcomes in patients with acute ischemic stroke caused by large vessel occlusion (AIS‐LVO). Prolonged venous transit (PVT), a visual qualitative VO marker on CT perfusion (CTP) time to maximum (Tmax) maps, has been associated with unfavorable 90‐day functional outcomes despite successful reperfusion. This study investigates the association between PVT and percent change on the National Institutes of Health Stroke Scale (NIHSS) among AIS‐LVO patients who have undergone successful reperfusion. Methods We performed a retrospective analysis of prospectively collected data from consecutive adult AIS‐LVO patients with successful reperfusion (modified Thrombolysis in Cerebral Infarction 2b/2c/3). PVT+ was defined as Tmax ≥10 s in the superior sagittal sinus, torcula, or both. The primary outcome was continuous NIHSS percent change and dichotomous NIHSS percent change ≥70%. Regression analyses were performed to assess the effect of PVT on NIHSS percent change. Results In 119 patients of median (IQR) age 71 (63–81) years, the admission and discharge NIHSS scores were significantly higher in PVT+ patients compared to PVT− patients (17 [14–23.5] vs. 13 [9.5–19], p = 0.011, and 7.5 [4–12] vs. 3 [1–7], p < 0.001, respectively). After adjusting for age, sex, hypertension, diabetes, atrial fibrillation, administration of intravenous thrombolysis (IVT), Alberta Stroke Program Early CT Scores (ASPECTS), mTICI 2c and/or 3, Tmax >6 s volume, and hemorrhagic transformation, PVT+ was significantly associated with lower NIHSS percent change (B = −0.163, 95%CI −0.326 to −0.001, p = 0.049) and was less likely to achieve higher than 70% NIHSS improvement (OR = 0.331, 95% CI 0.127–0.863, p = 0.024). Interpretation PVT+ was significantly associated with reduced neurological improvement despite successful reperfusion in AIS‐LVO patients, highlighting the critical role of VO impairment in short‐term functional outcomes. These findings further validate PVT as a valuable adjunct imaging biomarker derived from CTP for assessing VO profiles in AIS‐LVO.